Dėl asmeninių įvardžių dviskaitos kilmininko kai kurių formų kilmės - Rosinas, Albertas (Baltistica, 2006)
ON THE ORIGIN OF SOME GENITIVE DUAL FORMS OF PERSONAL PRONOUNS The article deals with the origin of the genitive dual forms mùma and jùma, which are personal pronouns used in the southern West Aukštaitian subdialect as well as in East Prussian Lithuanian texts and subdialects. Some scholars argue that the above forms are old dative-instrumental forms which acquired a genitive meaning in prepositional constructions only after the prepositions which govern the dative began to govern the genitive, i.e. when prie + dative → prie + genitive. The article puts forward the idea that the said dative forms obtained a genitive meaning long before the change in the prepositional government. This became possible by transforming the possessive construction with the subject in the dative + būti into ‘dative’ + noun: Mùma yra pamotė (‘She is a stepmother to us’) → Mùma pamotė (‘Our stepmother’), cf. Aš turiu pamotę (‘I have a stepmother’) → Mano pamotė (‘My stepmother’). The change of the meaning of these forms could also have been influenced by the atonic singular forms mi, ti, si used in the genitive, dative and accusative meanings. Had this change of meaning not occurred in an adjectival position before the change in the prepositional government, the constructions *iš muma, *nuo muma would hardly have arisen.